POSBAKUM'S ROLE IN PROVIDING LEGAL ASSISTANCE TO UNDERCOMFORTABLE COMMUNITIESIN STATE STATE COURT - Dewa Sujira; Muhammad Arif Sahlepi; Sumarno (PT. Radja Intercontinental Publishing, 2024)
Posbakum defends people who are less fortunate, whether because of limited information facilities or because some people still view law as a field of knowledge that is full of ins and outs and complexities so that it is difficult to learn, even though in law it applies that a person's ignorance of the law cannot be used as an excuse to free that person from legal demands. . The research method used is empirical research, field research at the Posbakum at the Stabat District Court and interviews with people who are deemed capable of answering questions relating to the problem of the role of the Posbakum in providing legal assistance to underprivileged communities. That in order to realize the idea of ​​a rule of law, the State has an obligation to guarantee everyone's right to obtain justice. In other words, the State must guarantee the provision of legal aid for the underprivileged so that no one is denied access to justice as mandated by the constitution. In several cases handled by legal advice from the Posbakum of the Stabat District Court, the Posbakum of the Stabat District Court has had permanent legal force.